RESPONS GURU KELAS TERHADAP SOSIALISASI PROGRAM LITERASI LITULIT DI SEKOLAH DASAR KOTA JAMBI - Muhammad Aqua Mutharik; Arisma Salwa Hilmana; Nurlis Anwary (STKIP Subang, 2025)
The LITULIT (10-Minute Literacy) program is a literacy habituation program designed to foster a culture of reading and writing in students through short literacy activities carried out routinely before learning begins. This study aims to describe the implementation of the LITULIT Program and analyze its impact on literacy habits, learning readiness, and student learning attitudes. The study used a descriptive qualitative approach with data collection techniques in the form of observation, teacher interviews, and documentation of student literacy journals. The research results show that the LITULIT Program is able to increase the consistency of students' reading habits, improve reading comprehension skills, and encourage students to express ideas in writing through simple reflections. Furthermore, this program contributes to developing students' discipline, focus, and learning independence. However, program implementation still faces obstacles in the form of limited reading material variety and differences in students' literacy abilities. Therefore, adequate literacy support and adaptive teacher mentoring are needed to ensure the program runs optimally and sustainably. Overall, the LITULIT (10-Minute Literacy) Program is effective as a practical and contextual literacy habit-building strategy to support the School Literacy Movement and strengthen the Pancasila Student Profile.